THE CONTRIBUTION OF FIRST LANGUAGE TRANSFER TO ENGLISH SENTENCES STRUCTURE AMONG SECOND LANGUAGE LEARNERS - Riska Febrianti; Rifa Salwa Rifa (Conscientia - Journal on Language, Literature, and Culture, 2026)
This study explores how first language (L1) transfer affects English sentence structure among five first-year students of the English Literature Study Program at Sebelas April University when translating Indonesian texts into English. Using Robert Lado’s theory of language transfer, the study identifies common structural errors caused by negative transfer, such as incorrect word order, misuse of articles, verb tense errors, and subject–verb disagreement. The data were collected through a translation task involving five Indonesian sentences and analyzed using a descriptive qualitative method. The findings show that most errors made by the participants reflect direct influence from Indonesian grammatical structures, while only one participant demonstrated evidence of positive transfer. These results indicate that L1 plays a significant role in shaping learners’ English sentence construction and highlight the importance of contrastive grammar instruction in second language learning.